Recommended educational approaches for teaching children with Attention Deficit Hyperactivity Disorder (ADHD) coordination and organization skills - Riga, Asimina; Ifanti, Theodora; Papayiannis, Nikolaos (IJRDO- Journal of Educational Research, 2017)
The main purpose of this article is to investigate and describe the difficulties faced by children with ADHD and to analyze the most appropriate educational approaches in relation to them. These approaches intend to help students reach a better coordination in the work they undertake each time as well as to improve their organizational skills in order to boost both their academic productivity and social performance. Behavioral strategies include both behavior reinforcement and self-monitoring teaching. To realize this objective a brief literature review has been conducted in order to provide concrete information and convincing arguments both from the Greek and international literature. Finally, although the expected positive effects of the objectives concerning the specific educational intervention are bibliographically confirmed, it is recommended that they be further examined through their application within classroom